A novel fluorescence immunosensor based on Förster resonance energy transfer between nitrogen and sulfur co-doped carbon dot functionalized silica nanospheres and Au@Ag NPs. (19th December 2018) - Cao, Jun-Tao; Zhang, Wen-Sheng; Wang, Hui; Ma, Shu-Hui; Liu, Yan-Ming
Abstract : A fluorescence immunosensor for PSA detection was developed based on the FRET between Si/NS-CDs and Au@Ag NPs. Abstract : A novel fluorescence (FL) immunosensor for prostate-specific antigen (PSA) detection was developed based on the Förster resonance energy transfer (FRET) between nitrogen and sulfur co-doped carbon dot functionalized silica nanospheres (Si/NS-CDs) and Au@Ag NPs. The strategy utilized the PSA primary antibody labeled luminescent Si/NS-CDs as donors and PSA secondary antibody labeled Au@Ag NPs as acceptors. In the presence of PSA, the bio-affinity of the antigen and antibody caused the Si/NS-CDs and Au@Ag NPs to approach at a close enough distance for the FL intensity of the Si/NS-CDs to decline owing to the FRET effect. By virtue of the excellent optical properties of the Si/NS-CDs nanoprobe, the quantitative analysis of PSA has been successfully realized using both FL spectroscopy and a naked-eye readout. The fluorometric results present the desirable analytical performance for PSA detection in the range from 5.0 pg mL −1 to 10 ng mL −1 with a detection limit of 0.95 pg mL −1 (S/N = 3). Moreover, satisfactory results for the determination of the PSA target in samples of human serum were obtained, showing the great promise of the method for application in biochemical analysis.